2019
DOI: 10.1021/acs.jpcb.9b05796
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Conformational and Energy Landscapes of KRAS Membrane Orientation

Abstract: Membrane reorientation of oncogenic RAS proteins is emerging as an important modulator of their functions. Previous studies have shown that the most common orientations include those with either the three C-terminal α-helices (OS1) or N-terminal β-strands (OS2) of the catalytic domain facing the membrane. OS1 and OS2 differ by the degree to which the effector-interacting surface is occluded by the membrane. However, the relative stability of these states and the rates of transition between them remained undete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 51 publications
5
38
0
Order By: Relevance
“…In some of these orientations, the G-domain is unable to interact with effectors because of the occlusion of the switch loops by the membrane. The simulations have also shown that the relative disposition of the HVR and the G-domain underpin membrane reorientation [58][59][60].…”
Section: Activation State Dependent Orientations Of Ras On the Membranementioning
confidence: 86%
See 1 more Smart Citation
“…In some of these orientations, the G-domain is unable to interact with effectors because of the occlusion of the switch loops by the membrane. The simulations have also shown that the relative disposition of the HVR and the G-domain underpin membrane reorientation [58][59][60].…”
Section: Activation State Dependent Orientations Of Ras On the Membranementioning
confidence: 86%
“…Following the original report on H-Ras [16], extensive MD simulations in recent years have shown that the G-domain of G12D [58], G12V [59], Q61H [60] and wild type K-Ras [61] directly interacts with membrane lipids via multiple distinct orientations. In some of these orientations, the G-domain is unable to interact with effectors because of the occlusion of the switch loops by the membrane.…”
Section: Activation State Dependent Orientations Of Ras On the Membranementioning
confidence: 99%
“…Following the original report on H-Ras [16], extensive MD simulations in recent years have shown that the G-domain of G12D [58], G12V [59], Q61H [60] and wild type K-Ras [61] directly interacts with membrane lipids via multiple distinct orientations. In some of these orientations, the G-domain is unable to interact with effectors because of the occlusion of the switch loops by the membrane.…”
Section: Activation State Dependent Orientations Of Ras On the Membranementioning
confidence: 97%
“…These results suggest that the two (Asn-Lys) or six (Asn-Lys-Ile-Glu-Ser-Gly) N-terminal residues in the Rab4a HRV linker domain contribute to limiting the intrinsic tethering potency of the G-domain through their interactions with the polar lipid headgroups. Considering that recent computational studies by molecular dynamics simulations of membrane-bound K-Ras, belonging to the Ras superfamily, reported the multiple orientation states of the K-Ras G-domain on the membrane surface that are affected by the C-terminal HVR linker and anionic membrane lipids (Prakash et al, 2016;Prakash and Gorfe, 2019;Neale and Garcia, 2020;Ngo et al, 2020), it is conceivable that the hydrophilic interactions between the N-terminal residues of the Rab4a HVR linker and anionic lipids may guide the G-domain into the specific "tetheringincompetent" membrane orientation.…”
Section: Critical Residues In the Hvr Linker Domain Of Rab4a For Regumentioning
confidence: 99%